The Influence of Family Education and Environmental Habits on Students' Environmental Consciousness: A Scientific Quantitative Study - Army Auliah; Vika Puji Cahyani; Achmad Romadin; Lukmanul Hakim Samada; Mohd Zulfakar Mohd Nawi (Universitas Negeri Semarang, 2026)
Environmental awareness is important for shaping sustainable behavior, and the family, as the first educator, plays a role in instilling environmental values and habits. This study aims to analyze the influence of family education and environmental habits on college students' environmental consciousness. The study used a quantitative correlational design with a sample of 58 chemistry education students from Universitas Negeri Makassar, Class of 2025, selected via simple random sampling. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression. The results showed that the independent variables (parental support for environmental education and issues, discussions about environmental issues, use of environmentally friendly products, and family involvement in environmental activities) did not have a significant influence on college students' environmental awareness. However, the overall contribution of these variables to college students' environmental awareness was low, with a coefficient of determination (R²) of 12.2%. This study concluded that although parental support and family environmental habits did not have a significant influence on students' environmental consciousness, their overall contribution was low.